Hepatitis B viremia in HIV-coinfected individuals under antiretroviral therapy - Weissmann,Leonardo (2019)
ABSTRACT Background: Antiretroviral therapy (ART) has decreased AIDS incidence and mortality, rendering comorbidities, such as hepatitis B more relevant for people living with human immunodeficiency virus (HIV). Since antiretroviral drugs may also inhibit hepatitis B virus (HBV) replication, analyzing the impact of ART on management of hepatitis B in this population is important. Objective: To assess HBV viremia among HIV/HBV coinfected individuals on ART and its associated factors. Method: For this cross-sectional study, HIV/HBV-coinfected individuals, aged over 18 years, who were on ART for over six months and receiving care at an outpatient clinic in São Paulo were recruited. Sociodemographic characteristics, information about viral exposure, clinical and laboratory data, including evaluation of liver fibrosis were obtained. Plasma HBV DNA was measured by polymerase chain reaction. Viral genome sequencing was conducted for genotyping and identification of drug resistance-conferring mutations if viral load exceeded 900 IU/mL. Results: Out of 2,946 patients who attended the clinic in 2015, 83 were eligible and 56 evaluated. Plasma HBV DNA was detected in 16 (28.6%) (95% CI: 18.0-41.3%), all on lamivudine and tenofovir treatment. HBV DNA detection was associated with lower education (p = 0.015), higher international normalized ratios (p = 0.045), history of an AIDS-defining illness [OR: 3.43 (95% CI: 1.10-11.50)], and HBeAg detection [OR: 6.60 (95% CI: 1.84-23.6)]. In contrast, a last CD4+ count above 500 cells/mm3 in the year prior to inclusion [OR: 0.18 (95% CI: 0.04-0.71)] and detection of anti-HBe [OR: 0.21 (95% CI: 0.04-0.99)] were negatively associated. Patients with HBV DNA above 900 IU/mL were infected with subgenotypes A1 (n = 3) and D2 (n = 1), and exhibited viral mutations associated with total resistance to lamivudine and partial resistance to entecavir. Conclusions: Despite being on ART, a significant proportion of HIV/HBV-coinfected individuals present HBV viremia. Characterization of factors that are associated with this finding may help professionals provide better management to these patients.